Approximative justice and cross-border evidence in the EU - Waldenström, Anna G. (Routledge, 2025)
"This book confronts the difficulties raised by cross-border evidence in order to propose a new understanding of justice as approximative. Can there be any common sense of justice across the European Union (EU)? This book takes up this question which is raised directly in cases where the hearing of cross-border evidence encounters national and linguistic differences. The interpretive challenges this introduces impacts the possibility of justice in a way that, the book argues, cannot be resolved with recourse to some ideal of harmonisation that would simply flatten these differences. Rather, these cases - taken here from Sweden and France - raise a practical, but also a theoretical, question about how justice can be done. In response, the book draws on contemporary theorisations of justice to argue against a common sense of justice in the sense of what would be a correct legal judgment. In its place, the book elaborates an idea of justice that maintains, rather than collapsing, the differences presented in cases of cross-border evidence; and which therefore aims to be 'approximative', or 'good enough', rather than simply correct. This book will be of interest to readers in legal theory, socio-legal studies, comparative law and European Union law"--